Aggregation of Au(i)-complexes on amorphous substrates governed by aurophilicity. Issue 39 (20th September 2019) - Gründlinger, Petra; Györök, Michael; Wolfmayr, Sebastian; Breuer, Tobias; Primetzhofer, Daniel; Bruckner, Barbara; Monkowius, Uwe; Wagner, Thorsten
Abstract : 2-Naphthylisonitrile–gold(i )-chloride can be evaporated without decomposition and form highly ordered thin films on substrate surfaces resembling the solid state structure. Abstract : In single crystals of 2-naphthylisonitrile–gold(i )-halide (halide = Cl, Br, I) complexes, Au⋯Au distances are found to be significantly shorter than twice the van der Waals radius, indicating attractive interactions between gold atoms in adjacent molecules. In the particular case of the studied 2-naphthylisonitrile–gold(i ) complexes, homodimers are the common structural motifs, in which the linearly coordinated gold exhibits a crossed swords arrangement with the Au atoms of two molecules being at the intersection point. The crossed swords motif is preserved upon physical vapour deposition of both the chlorine and bromine derivatives on amorphous substrates like glass and glassy carbon. The determined activation energies of desorption for the chlorine (0.9 eV) and the bromine (1.2 eV) derivative are comparable to that of unsubstituted naphthalene. Using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and ion scattering (RBS), we confirmed the chemical integrity of the molecules in thin films and revealed the orientation of the crossed swords dimers with respect to the substrate surface.